Real‐world outcomes of sipuleucel‐T treatment in PROCEED, a prospective registry of men with metastatic castration‐resistant prostate cancer - Higano, Celestia S. (Cancer, 2019)
BACKGROUND: The large registry, PROVENGE Registry for the Observation, Collection, and Evaluation of Experience Data (PROCEED)(NCT01306890), evaluated sipuleucel‐T immunotherapy for asymptomatic/minimally symptomatic metastatic castration‐resistant prostate cancer (mCRPC). METHODS: PROCEED enrolled patients with mCRPC receiving 3 biweekly sipuleucel‐T infusions. Assessments included overall survival (OS), serious adverse events (SAEs), cerebrovascular events (CVEs), and anticancer interventions (ACIs). Follow‐up was for ≥3 years or until death or study withdrawal. RESULTS: In 2011‐2017, 1976 patients were followed for 46.6 months (median). The median age was 72 years, and the baseline median prostate‐specific antigen level was 15.0 ng/mL; 86.7% were white, and 11.6% were African American. Among the patients, 1902 had 1 or more sipuleucel‐T infusions. The median OS was 30.7 months (95% confidence interval [CI], 28.6‐32.2 months). Known prognostic factors were independently associated with OS in a multivariable analysis. Among the 1255 patients who died, 964 (76.8%) died of prostate cancer (PC) progression. The median time from the first infusion to PC death was 42.7 months (95% CI, 39.4‐46.2 months). The incidence of sipuleucel‐T–related SAEs was 3.9%. The incidence of CVEs was 2.8%, and the rate per 100 person‐years was 1.2 (95% CI, 0.9‐1.6). The CVE incidence among 11,972 patients with mCRPC from the Surveillance, Epidemiology, and End Results–Medicare database was 2.8%; the rate per 100 person‐years was 1.5 (95% CI, 1.4‐1.7). One or more ACIs (abiraterone, enzalutamide, docetaxel, cabazitaxel, or radium 223) were received by 77.1% of the patients after sipuleucel‐T; 32.5% and 17.4% of the patients experienced 1‐ and 2‐year treatment‐free intervals, respectively. CONCLUSIONS: PROCEED provides contemporary survival data for sipuleucel‐T–treated men in a real‐world setting of new life‐prolonging agents, which will be useful in discussing treatment options with patients and in powering future trials with sipuleucel‐T. The safety and tolerability of sipuleucel‐T in PROCEED were consistent with previous findings.